The deficiency of myelin in the mutant taiep rat induces a differential immune response related to protection from the human parasite Trichinella spiralis - Nava-Castro, Karen Elizabeth (PLoS One, 2020)
Taiep rat is a myelin mutant with a progressive motor syndrome characterized by tremor, ataxia, immobility episodes, epilepsy and paralysis of the hindlimbs. Taiep had an initial hypomyelination followed by a progressive demyelination associated with an increased expression of some interleukins and their receptors. The pathology correlated with an increase in nitric oxide activity and lipoperoxidation. In base of the above evidences taiep rat is an appropriate model to study neuroimmune interactions. The aim of this study was to analyze the immune responses in male taiep rats after acute infection with Trichinella spiralis. Our results show that there is an important decrease in the number of intestinal larvae in the taiep rat with respect to Sprague-Dawley control rats. We also found differences in the percentage of innate and adaptive immune cell profile in the mesenteric lymphatic nodes and the spleen that correlated with the demyelination process that took place on taiep subjects. Finally, a clear pro-inflammatory cytokine pattern was seen on infected taiep rats, that could be responsible of the decrement in the number of larvae number. These results sustain the theory that neuroimmune interaction is a fundamental process capable of modulating the immune response, particularly against the parasite Trichinella spiralis in an animal model of progressive demyelination due to tubulinopathy, that could be an important mechanism for the clinical course of autoimmune diseases associated with parasite infection.